2022
DOI: 10.1155/2022/7967294
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Copper Nanoparticles Using Withania somnifera and Its Antioxidant and Antibacterial Activity

Abstract: This study employed green chemistry to synthesize copper nanoparticles (CuNPs) using fresh root extract of Withania somnifera. The size, shape, morphology, and stability of resultant CuNPs were investigated by UV-Vis spectroscopy, FTIR, transmission electron microscopy (TEM), and energy-dispersive spectrophotometer. Crude extracts were assessed phytochemically to determine the presence of alkaloids, flavonoids, phenols, saponins, steroids, and tannins. The UV-Vis absorption spectra show maximum absorption at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The sharp peak at 330 nm during UV-Vis was due to the surface Plasmon resonance phenomenon (Figure 2). Our results of characterization related to UV-Vis are in accordance with the earlier studies of Shanmugapriya et al [41] who showed that UV-Vis of green synthesized copper oxide nanoparticles from Withaniasomnifera was 330 nm. Scanning electron microscopy showed that nanoparticles were neither aggregated nor clumped (Figure 3A) and the presence of elemental copper was confirmed by EDX (Figure 3B).…”
Section: Discussionsupporting
confidence: 92%
“…The sharp peak at 330 nm during UV-Vis was due to the surface Plasmon resonance phenomenon (Figure 2). Our results of characterization related to UV-Vis are in accordance with the earlier studies of Shanmugapriya et al [41] who showed that UV-Vis of green synthesized copper oxide nanoparticles from Withaniasomnifera was 330 nm. Scanning electron microscopy showed that nanoparticles were neither aggregated nor clumped (Figure 3A) and the presence of elemental copper was confirmed by EDX (Figure 3B).…”
Section: Discussionsupporting
confidence: 92%
“…This observation emphasises the remarkable capacity of Citrullus colocynthis peel extract to effectively cap and stabilise CuNPs. 30 Using the UV-vis spectral data, the band gap energy was calculated according to Tauc's relation (Eq. 1):…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of the crude extract and silver nanoparticles was assessed using the Agar diffusion technique, as described by Ali et al ., Ahmad et al ., Shanmugapriya et al . [ 24 26 ] with slight modifications. 5 Muller Hinton Agar (5.6 grams) was dissolved in 200 milliliters of distilled water, heated, and autoclaved under specific parameters.…”
Section: Methodsmentioning
confidence: 99%